Metamorphosis of Benthic Invertebrate Larvae: A Sensitive Indicator for Detection of Changes in Marine Environmental Quality - Xuelei Zhang (The Scientific World Journal)
Many marine coastal ecosystems are threatened by increasing waste discharge, and bioassays are needed because chemical and physical tests alone are not sufficient to assess potential effects on aquatic biota. In light of the fact that larval metamorphosis of benthic invertebrates is usually very sensitive to environmental changes, this paper reviews sensitivity comparisons of larval metamorphosis with other common bioassays in different species and those in different developmental stages of the same species, and it discusses the potential use of larval metamorphosis as an indicator of marine environmental quality.